Bortom vänster- och högerdikotomin: Politiska attityder och värderingar hos svenska väljare - Diffner,Erik; Isaxon,Anna (2015)
This survey study explored the nuance behind the left-right ideological dichotomy. This was done by empirically studying the differences both between and inside the political left and right. Six scales were used to measure the political attitudes and basic personal values connected to change and equality. These were compared with voting in the Swedish national elections in 2010. The participants were divided into two groups with 314 participants in one and 286 in the other. Differences in attitudes and values both between and inside the political left and right was hypothesized, differences mainly inside the political left regarding attitudes and values toward social change. The empirical study gave support for the hypothesis. The results showed that the change dimension were not associated to the left-right dimension in Sweden, the equality dimension, however, was. Differences regarding both attitudes and values were found both between and inside the political blocks. The main differences was found within the change dimension were the Social democrat voters where significantly less positive towards social change than were the Environment party voters and the Left party voters. The Social democrats had more attitudes and values in common with the voters of the Folk party and Center party than the Environment party and the Left party. The consequences of these results on the Swedish block policies are further discussed.
Keywords: röstning; politiska attityder; Politisk psykologi; personliga värderingar; ideologi; Sverige; Political psychology; basic personal values; political attitudes; voting; ideology; Sweden